Características fenotípicas de 44 progênies de espinheira-santa (Maytenus ilicifolia Mart. ex Reiss) cultivadas no município de Ponta Grossa, PR - Radomski, M. I.; Scheffer, M. C.; Büll, Leonardo Theodoro [UNESP] (My University, 2008)
Due to the confirmation of its medicinal properties, the demand and the area planted with 'espinheira-santa' have been increasing. However, there are no sources of propagation material with known characteristics. Progenies of Maytenus ilicifolia Martius ex Reiss (espinheira-santa), originating from Southern Brazil have been analyzed, and currently comprise a germplasm inventory for the species. Studies included the assessment of in natura growth features (height and production of biomass canopy) and plant chemistry (lignin, phenols and mineral element contents), and targeted the creation of a data base, characterizing populations/progenies to be used in future selection and breeding programs of the species. Among the features assessed, were considered desirable the ones related to productivity (high foliar mass to branch mass ratio) and also the absence of thorns on the leaves. High total phenol and tannin content were observed in all the progenies assessed and these features is desirable as long the absence of toxic effects and preservation of the therapeutic quality of the plant medicinal elements produced can be proved.
Phenotipic traits of 44 progenies of Maytenus ilicifolia Martius ex Reiss cultivated in the municipality Ponta Grossa, Parana State, Brazil
Keywords: Genetic variability; Lignin; Meytenus ilicifolia; Mineral elements; Phenols; phenol; tannin; biomass; Brazil; controlled study; genetic trait; genetic variability; Maytenus; maytenus ilicifolia; medicinal plant; nonhuman; phenotype; progeny; Maytenus ilicifolia